Islamic Monetary Tradition and Practice: A Historical Approach - Muhammad Afriansyah Hidayah; Asyari Hasan (Al-'Adl, 2022)
This study aims to analyze monetary discourse from a historical perspective. This research focuses on how to monitor problems has been explored since the time of the Prophet until today. This study uses a historical research design. The technique used in analyzing the data is narrative through literature study. The finding in the study show that the dinar and dirham also allow speculation, but in the end, they do not because they have intrinsic value. From period to period, began to determine the size make design changes and quality improvements to achieve a reasonable goal of reducing counterfeiting money. Economic and political stability is the real goal to be completed to increase.